A Survey of Women's Awareness of and Reasons for Lack of Postfracture Osteoporotic Care. Issue 8 (19th April 2017) - Boudreau, Denise M.; Yu, Onchee; Balasubramanian, Akhila; Wirtz, Heidi; Grauer, Andreas; Crittenden, Daria B.; Scholes, Delia
Abstract : Objectives: To identify women's beliefs and other factors associated with lack of osteoporosis (OP) pharmacotherapy (OP‐RX) during the 6 months after a fragility fracture, including the woman's perspective on fracture risk, OP, and treatment. Design: Cross‐sectional. Setting: Group Health Cooperative, a mixed‐model delivery system. Participants: Female Group Health Cooperative enrollees aged 55 and older with an OP‐related fracture according to diagnostic and procedure codes from January 1, 2013, to March 30, 2014 (N = 985). Measurements: OP‐RX and participant characteristics were ascertained from electronic health records including medications dispensed. A mailed survey was used to obtain data on health behaviors; OP‐related history; concern about, knowledge of, and perceived risk of future fracture; beliefs about OP‐RX; sources of information on OP; postfracture discussions with providers; and provider recommendations. Results: The response rate was 73%. Of 634 eligible respondents, 84% did not undergo OP‐RX during the 6 months after fracture. Fewer than 20% of women thought that OP caused their fracture, 52% did not think they were at risk of future fracture, and 75% did not think or know whether OP‐RX reduces risk of fracture. Knowledge about OP and the benefits of treatment was higher in the 16% of women who underwent OP‐RX after their fracture. Women reported low levels of engagement with their healthcare providers regarding OP and fracture risk management. Conclusion: These findings suggest low awareness about OP and its contribution to fracture risk, lack of understanding about the benefits of pharmacotherapy, and limited discussion about OP with primary care physicians. Information about individual's beliefs and knowledge gaps can help design targeted patient and provider education to improve treatment rates.